Market Governance and Ecological Sacrifice in Tobacco Farming: Environment–Livelihood Trade-Offs and Hybrid Institutions in The Besuki Raya Region East Java Province, Indonesia - Herman Cahyo Diartho; Agus Luthfi; Rhamanda Try Muktianto; M. Iqbal Fardian (PPJP ULM, 2026)
Tobacco farming in Besuki Raya, East Java, demonstrates how environmental degradation in smallholder agrarian systems is shaped by market power, livelihood dependence, and hybrid institutional arrangements. This study examines how economic governance structures influence environmentally consequential production practices and environment–livelihood trade-offs in tobacco farming. The study was conducted in the Besuki Raya region of East Java, Indonesia, covering Jember, Lumajang, Bondowoso, and Banyuwangi as major tobacco-producing districts. A qualitative political–economic ethnographic design was employed. Data were collected between March and November 2025 through 54 in-depth interviews, eight focus group discussions involving 56 participants, 36 field observation visits, document analysis, and limited netnographic observation of six WhatsApp and Facebook farmer communities. Data were analysed using ATLAS.ti 23 through open, axial, and selective thematic coding. The findings show that formal regulations, market mechanisms, cooperatives, and patron–client relations stabilise short-term livelihoods while reproducing environmentally intensive farming. Warehouse-based grading and advance financing encourage chemical input use, accelerated production, and quality compliance because prices and debt repayment are determined after harvest. This study contributes to ecological economics by showing that environmental degradation is embedded in market governance rather than arising from isolated farmer behaviour or technical inefficiency alone.